1997
DOI: 10.1016/s0005-2736(97)00027-8
|View full text |Cite
|
Sign up to set email alerts
|

Grafted poly-(ethylene glycol) on lipid surfaces inhibits protein adsorption and cell adhesion

Abstract: Monolayers of dipalmitoyl-phosphatidylethanolamine (DPPE) mixing with various mole percentages of distearoyl-phosphatidylethanolamine (DSPE)-conjugated poly-(ethylene glycol) (PEG m.w. 750-5000) were deposited on DPPE-coated glass surfaces by the Langmuir-Blodgett method. Increasing percentages of grafted PEG in these supported lipid surfaces increasingly inhibit the adsorption of bovine serum albumin (BSA), laminin, and fibronectin. Increasing percentages of grafted PEG also inhibit the adhesion of erythrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
214
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(231 citation statements)
references
References 22 publications
15
214
0
1
Order By: Relevance
“…[25][26][27] There are previous reports that the surface modification of biomaterials with PEG appreciably reduces thrombogenicity. 25,[28][29][30][31][32] Thus, it is widely accepted that PEG shields the cationic surface of biomaterials, reducing their thrombogenicity. 31 In this study, the PEG-b-P[Asp(DET)] micelle system showed no agglomeration even in the presence of blood components including serum albumin (Table 1 and Figure 4), platelets ( Figure 5) and erythrocytes ( Figure 6), whereas BPEI and P[Asp(DET)] polyplexes definitely showed the aggregate formation due to their positively charged character under the same conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] There are previous reports that the surface modification of biomaterials with PEG appreciably reduces thrombogenicity. 25,[28][29][30][31][32] Thus, it is widely accepted that PEG shields the cationic surface of biomaterials, reducing their thrombogenicity. 31 In this study, the PEG-b-P[Asp(DET)] micelle system showed no agglomeration even in the presence of blood components including serum albumin (Table 1 and Figure 4), platelets ( Figure 5) and erythrocytes ( Figure 6), whereas BPEI and P[Asp(DET)] polyplexes definitely showed the aggregate formation due to their positively charged character under the same conditions.…”
Section: Discussionmentioning
confidence: 99%
“…25,[28][29][30][31][32] Thus, it is widely accepted that PEG shields the cationic surface of biomaterials, reducing their thrombogenicity. 31 In this study, the PEG-b-P[Asp(DET)] micelle system showed no agglomeration even in the presence of blood components including serum albumin (Table 1 and Figure 4), platelets ( Figure 5) and erythrocytes ( Figure 6), whereas BPEI and P[Asp(DET)] polyplexes definitely showed the aggregate formation due to their positively charged character under the same conditions. It should be noted that PEG-b-P[Asp(DET)] micelle showed no platelet and erythrocyte aggregation even at a high N/P ratios, whereas P[Asp(DET)] and BPEI polyplexes induced platelet and erythrocyte aggregation even at low N/P ratios, such as 5.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these molecules have been used to physically modify the surfaces of SWNHs, thereby reducing non-specific binding onto SWNH aggregates. 96,97 Different types of PEG-based macromolecules showed different dispersion abilities with the SWNH aggregates. 98 When PEG-doxorubicin was used to disperse SWNH aggregates, the as-obtained conjugates induced the apoptosis of cancer cells due to the anticancer pharmacodynamics of doxorubicin.…”
Section: Figurementioning
confidence: 99%
“…15,18,19) With the increase of concentration of PEG-lipid on the liposomal membrane, serum protein prevents binding to the liposome membrane because of PEG-lipids overlapping each other. [20][21][22] As a result, it is considered that PEG-modified liposomes have a long circulation time. 8,9) However, the amount of PEG-lipids inserted into the liposome membranes is limited, and FALT forming around the liposomes reaches a plateau, 23) so it was considered that increasing FALT was difficult.…”
Section: Mixing Two Different Pegs Tomentioning
confidence: 99%